Psychological Profile of Sasang Typology: A Systematic Review. (2009) - Chae, Han; Park, Soo Hyun; Lee, Soo Jin; Kim, Myoung-geun; Wedding, Danny; Kwon, Young-Kyu
Abstract : A systematic review of studies related to the psychological characteristics of Sasang types was conducted with the goal of delineating generalizable psychological profiles based on Sasang typology, a traditional Korean medical typology with medical herbs and acupuncture that is characterized as personalized medicine. Journal articles pertaining to Sasang typology were collected using five electronic database systems in Korea and in the USA. As a result, 64 potentially relevant studies were identified and 21 peer-reviewed research articles that employed psychometric inventories were included. Beginning with the use of the Minnesota Multiphasic Personality Inventory in 1992, Myers-Briggs Type Indicator, NEO-Personality Inventory, Temperament and Character Inventory and other personality assessment tools were employed in the identified studies. Because data synthesis could not be carried out due to the heterogeneity of the studies, the present review article sought to delineate the mutual relevance of the studies based on research results pertaining to the correlation between the aforementioned psychological assessment instruments. Results of the review indicate that two super-factors, Extraversion and Neuroticism, serve as the foundation in regards to delineating personality constructs, such that the So-Yang type scored high on the Extraversion dimension and low on the Neuroticism dimension, while the So-Eum type scored low on the Extraversion dimension and high on the Neuroticism dimension. The present systematic review indicates that Sasang typology shares similarities with the Western psychological tradition.